Environmental Sustainability: A Major Component of Sustainable Development - Islam Md. ZIAUL; Wang SHUWEI (International Journal of Environmental, Sustainability, and Social Science, 2023)
Without embracing environmental sustainability (ES), the universal concept of Sustainable Development Goals (SDGs) cannot be achieved in today's world. As an inseparable part of SDGs, ES can help the nations to fulfil the goal of Agenda 2030. The world, particularly the developing countries, is now encountering several environmental problems, including carbon dioxide (CO2) emission, hazardous pollution, climate change, global warming, floods, droughts, deforestation, excessive and less rainfall crisis, scarcity of food, water and other natural resources, misuse and overconsumption of natural resources, and loss of biodiversity. All these factors heavily impact our natural environment and cause irreparable loss. Our study finds that with unsustainable socio-economic development, environmental degradation is rising worldwide. We argue that human activities in the name of development are the main reasons for destroying the environment and natural resources. In this study, we explore that despite taking significant initiatives by the United Nations engaging the member countries to protect the earth from the aboementioned environmental problems, these problems are still prevalent in many countries in the world. Our study finds that irresponsible human activities primarily hinder sustainable development progress, which is essential for present and future generations. In this article, we find that embracing the environmental sustainability approach for all countries is necessary to ensure holistic sustainable development.